United States : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in the United States during 1992-96. The paper briefly describes improvements in the national income and product accounts (NIPA) and some of their implications for the analysis of long-term trends in U.S. investment and saving. The paper highlights that the effect of the 1990-92 recession on employment was considerably less severe than the effect of the 1981-82 recession. During the 1990-92 recession, employment fell by 1 1\2 percent, compared with a drop of 3 percent during the 1981-82 recession.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet